RANCANG BANGUN DECISION SUPPORT SYSTEM UNTUK PEMILIHAN RUTE PENGIRIMAN PAKET PADA PERUSAHAAN PENYEDIA JASA LOGISTIK - Bilal Ahmadi; devi jayawati (Jurnal Manajemen Industri dan Logistik (JMIL), 2017)
Traveling Salesman Problem (TSP) is a well-known route optimization problem in which a set of customers is visited only once and all demands are satisfied within single route. Package delivery by a courier company can be considered into this type of problem. While many of the previous research had been conducted, the application of the solutions were limited due to unreal distance measure. This paper developed a decision support system for route optimization using free online maps from Google and Google Maps Application Programming Interface (API). Genetic Algorithm was employed to generate solutions within relatively short time. Furthermore, the solutions was viewed as a function of distance and time. There were some limitations from Google in case of acquiring distance data with the free of charge mechanism. Future research can tackle this backdraw by putting more customer points. Other heuristic methods could also be used for comparison purpose